Alkaline earth metal catalyzed cascade, one-pot, solvent-free, and scalable synthesis of pyranocoumarins and benzo[b]pyrans. Issue 13 (25th March 2015) - Yaragorla, Srinivasarao; Saini, Pyare Lal; Singh, Garima
Graphical abstract: Abstract: Ca(OTf)2 catalyzed, cascade, one-pot, conjugate addition and annulation of various nucleophiles to the α, β-unsaturated carbonyl compounds for the synthesis of biologically potent pyranocoumarins and benzo[ b ]pyrans has been illustrated. This one-pot, solvent-free, green-synthesis employs simple reaction conditions, with high yields and endures the substrate diversity.